Durable Response to Immunotherapy With Antiangiogenic Drug in Large-Cell Lung Carcinoma With Multiple Fulminant Postoperative Metastases: A Case Report - Luo, Zhilin; Zhang, Hong; Xiao, Yajie; Wang, Rui; Zhang, Liping; Huang, Chenglu; Cao, Yu; Sun, Chao; Zhao, Yongtian; Lin, Hanqing; Wu, Dongfang; Wang, Tianhu (Frontiers in Oncology, 2021)
Immunotherapy alone or chemo-immunotherapy has recently been recommended for treating advanced lung carcinoma in patients without driver mutations. However, the efficacy of immunotherapy and molecular mechanisms in large-cell lung cancer (LCLC) remains unclear. Here, we reported a rare case of multiple fulminant postoperative body and mouth metastases in LCLC treating with combination immunotherapy. Initially, the patients was diagnosed as early stage LCLC and underwent a radical resection of the right lower lobe. Just one month later, multiple fulminant body and mouth metastases appeared in the right upper arm, right elbow, right waist and tongue root. Meanwhile, serum neuron specific enolase (NSE) concentration dramatically increased from 12.12 ng/ml to 30.14 ng/ml. Immumohistochemistry findings demonstrated a high PD-L1 expression with tumor proportion score (TPS), while next-generation sequencing (NGS) indicated moderate tumor mutational burden (TMB) levels and gene mutations in PBRM1 L1230P and TP53 L194R of both foci. Besides, loss of heterozygosity (LOH) at human leukocyte antigen (HLA) class I (HLA-A*02:03, HLA-B*55:02 and HLA-C*12:03) were detected in the right upper arm metastasis, which may facilitate malignant postoperative metastases in this case. Interestingly, this patient received combination therapy with anti-PD1 sintilimab, and achieved a partial response for at least 12 months. Using an integrated computational method, the mutant peptide TEIPENDIPL derived from PBRM1 L1230P was predicted to be a specific neoantigen and can still be presented by HLA-B*40:01. This case suggested that malignant postoperative metastases in LCLC might be facilitated by LOH at HLA. Moreover, immunotherapy plus antiangiogenic drugs can provide an alternative therapeutic option for these advanced LCLC patients without common gene mutations.